Mississippi - Mills, Jordan (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2017)
"This book uses maps, full color photographs, and easy-to-read text to introduce the state of Mississippi"--
Different countries
Includes bibliographical references and index
1 2 13
Keywords: Mississippi -- Juvenile literature